Development of a Wire Mesh Composite Material for Aerospace Applications - Bikkina, S. C. A.; Jayasree, P. V. Y. (Engineering, Technology & Applied Science Research, 2022)
The electrical conductivity of Fiber-Reinforced Polymers (FRPs) may be used to reduce the dangers of lightning strikes, radar radiation, and aerial radio frequency transmitters. Metal Matrix Composites (MMCs) were created to guard against Electromagnetic Interference (EMI) in the aircraft’s electric and electrical systems. High-Intensity Radiated Field Protection (HIRFP) aircrafts are required to be manufactured from a metal matrix consisting of Al6061, Al2O3, and Fly Ash (FA) to keep up with the ever-increasing needs of industry. The current work considered three MMC combinations. MMC1 is AL6061+10% and Al2O3+5% FA, MMC2 consists of AL6061+15 and Al2O3+5% FA, and MMC3 of AL6061+20% and Al2O3+5% FA. These MMCs made the shielding more effective at different percentages. The material electrical properties were interpreted based on experiments. Analytical approaches include the testing of the electrical parameters of materials to measure the shielding effectiveness. The calculated shielding efficiencies MMC1-55.7dB, MMC2-57.2dB, and MMC3-59.1dB allow the composites to be employed in aircrafts. This indicates that, for specific applications like HIRFPs, the constructed MMCs perform well.